Zhou history unearthed : the bamboo manuscript Xinian and early Chinese historiography - Pines, Yuri (Columbia University Press, 2020)
"Pines uses a set of bamboo manuscripts from the Warring States period (453-221 BCE) to reappraise early Chinese historiography. He begins with a survey of the field prior to the paleographic revolution, and then explains how these discoveries shed new light on the questions related to the production, circulation, and audience of historical texts in early China, their different political, ritual, and ideological usages, and their roles in the cultural and intellectual dynamics of China's extraordinarily vibrant pre-imperial age. The second half of the book consists of a translation of Xinian (String of Years) from the state of Chu, the most notable of the new texts"--